The Future of Things: A Comprehensive Overview of Internet of Things History, Definitions, Technologies, Architectures, Communication and beyond - Mphale, Ofaletse; Gorejena, Karikoga Norman; Nojila, Olebogeng (Journal of Information System and Informatics, 2024)
This paper explores the multifaceted world of IoT, exploring its historical evolution, core definitions, enabling technologies, architectural considerations, communication models and future predictions. Moreover, the paper critically scrutinises the potential benefits and challenges associated with IoT adoption. This study employed a systematic literature review (SLR) methodology to review existing literature between January 2020 and January 2024 on IoT technology. 20 relevant studies out of an initial pool of 45,312 studies were reviewed. The study followed the established Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) framework to ensure a rigorous and unbiased selection process. Findings revealed the lack of a universally accepted definition for IoT and significant variations in architectural models across scholarly works. Moreover, the study acknowledges the complex and ever-evolving nature of IoT technology, recognising its early stages of development. This dynamic technological landscape calls for continuous exploration of future research. Findings will provide valuable insights for academics, researchers, and industry professionals interested in the understanding the intricate technical landscape of IoT and its development. Moreover, by providing insights into growth predictions, benefits, and existing challenges, this will empower stakeholders to navigate the evolving IoT landscape and contribute to its future progress.